Synthesis and identification of Five Membered Rings Heterocyclic Compounds Derived from Trimethoprim - Nief, Olfat A; Alzahawy, Hala M G; Abdallah, Ebtihal K; Attia, Ali M (Al-Nahrain Journal of Science, 2018)
This study includes the preparation and identification of five membered rings Hetrocyclic Compounds derived from Trimethoprim by reaction Schiffs, bases(1a-h)(prepared by reaction some aromatic aldehyde with Trimethoprim using Microwave technique) with Hydroxy acidic acid (Glycolic acid), the prepared compounds were identified by I.R spectroscopy and some of them by NMR spectroscopy and C.H.N.S micro analysis.